2007
DOI: 10.1164/rccm.200602-256oc
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CC Chemokine Receptor 6 in Host Defense in a Model of Invasive Pulmonary Aspergillosis

Abstract: Rationale: Invasive aspergillosis is a severe fungal infection afflicting immunocompromised patients, particularly patients with neutrophil defects. CCR6, a ␤-chemokine receptor, mediates migration of dendritic cells (DCs) and several lymphocyte subsets to sites of epithelial inflammation, but its role in infections has not been examined extensively. Objectives: To test the hypothesis that CCR6-mediated leukocyte recruitment is necessary for effective host defense in neutropenic hosts with invasive pulmonary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 70 publications
2
77
0
Order By: Relevance
“…DCs are an important effector cell during invasive aspergillosis. The Mehrad group showed that CCR6-deficient mice were significantly more susceptible to invasive aspergillosis than were CCR6-sufficient mice (15). CCR6 and its ligand, CCL20, are responsible for the migration of immature DCs to sights of inflammation, including the lung (16,17,41,42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DCs are an important effector cell during invasive aspergillosis. The Mehrad group showed that CCR6-deficient mice were significantly more susceptible to invasive aspergillosis than were CCR6-sufficient mice (15). CCR6 and its ligand, CCL20, are responsible for the migration of immature DCs to sights of inflammation, including the lung (16,17,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…4). It has been previously reported that DCs provide protection against invasive aspergillosis and that mice lacking adequate numbers of DCs are susceptible to disease (15). Therefore, antifungal responses in CCR7 Ϫ/Ϫ chimeras appear to be the result of an enhanced accumulation of DCs.…”
Section: Wild-type or Ccr7mentioning
confidence: 98%
See 2 more Smart Citations
“…In vivo neutrophil depletion was induced by intraperitoneal administration of 400 mg of monoclonal antibody (mAb) against Ly6G (clone 1A8; Bio X Cell, West Lebanon, NH) or isotype control mAb (clone 2A3; Bio X Cell) as described (20). Methods for tissue harvest (21), bronchoalveolar lavage, and isolation of bone marrow neutrophils (22) and histology (19,21) have been described previously.…”
Section: Methodsmentioning
confidence: 99%